Kickstart Your Creativity: the ideas book - Mike Hutcheson (Wisdom tree, 2006)
Illustrated by cartoons, this is a collection of 84 witty stories exploring proven ways of solving problems. Some are based on historical events and others on the authors' acute observations of what makes creative people tick.